O Projeto Comprova e a mediação da informação em tempos de pós-verdade e de fake news - Maia, Juliana Galvão de Matos Brito (2023)
In post-truth times, misleading news – or as it is better known, fake news – is responsible for major changes in relationships between people. Social networks have transformed the form of communication, making it more agile, simple and trivial. Events such as Donald Trump'selections and the Brexit plebiscite are considered by international analysts as the beginning of the most forceful form of change in reality through the spread of fake news. In Brazil, the 2018 elections were also broadcast on disinformation. After these facts, the planet has experienced a Covid-19 pandemic. And this became yet another ingredient to fuel the wave of misinformation. We live in times of infodemic. A lot of information in a post-truth scenario, where personal opinions are worth more than real facts. Based on the characteristics of Information Science (IS) and Communication, this research analyzes the Comprova Project, its news verifications and the ways in which it contributes to combating misinformation and the like. From a bibliographical survey based on the theories of information and information mediation, a content analysis was carried out on the news verifications of the Comprova Project for the year 2021. It is demonstrated how the mediation carried out from the websites of News verification is part of the context of information mediation, as presented in the CI, combating the spread of misinformation in contemporary times.